Representasi Poligami dalam Film Bismillah Kunikahi Suamimu : Analisis Semiotika Roland Barthes - Syahbina Laila Wahda; Rindana Intan Emeilia (Institut Nalanda, 2024)
Films can have a strong emotional impact and connect viewers with personal stories. Society's perspective regarding polygamy in films is often negative, which ends in discrimination against third parties. One of the films that tells the story of polygamy is the film Bismillah Kunikahi Suamimu. A film that invites viewers not to think negatively about polygamy. From this problem, the author is interested in studying the representation of polygamy using Roland Barthes' semiotic theory, as well as examining how polygamous life does not have a negative ending. The method used in this research is descriptive qualitative with analysis of Roland Barthes' semiotic theory examining the signs in this film and the pressure to search for meaning in denotation, connotation and myth. The data collection techniques used in this research are observation, documentation and interviews. The results of the research shown are several meanings of denotation, connotation and myth that represent polygamy in the house steps and shows the importance of exploring further the meaning of polygamy as a whole, both in terms of conditions, reasons and impacts. Other results show that in the film Bismillah Kunikahi Suamimu, polygamy can be carried out if the husband can fulfill the requirements and clear reasons and the husband can treat his wives fairly.